The integration of affective domains in French language learning: translating Molière into Malay - Abdul Halim, Hazlina (Universiti Malaysia Sarawak, 2022)
Translation is the communication of meaning by converting the source language to the target language. The discipline requires excellent mastery and control of both source and target language, as well as their affective values as in the cultures of both languages. As translation includes the high order thinking skills, the teaching of learning of translation is normally conducted using a traditional method. Hence, this research evaluates the effectiveness of theatre-based task in the learning of French-Malay translation. The respondents for the study were 54 French Language Studies students at Universiti Putra Malaysia. The translation theater project involves four phases, which are the translation of the Molière theater script Fourberries de Scapin to Malay, the selection of characters for the theater play, the management of the play, and the insertion of the script into the theater video. It was found that the theater task was well received by the respondents and effective as to enhance their team management skills (TS), creative thinking problem solving (CTPS), psychomotor (P6), communication skills (CS) as well as their cognitive skills (C5). Subsequently, the respondents reported putting their theoretical learning of the translation strategies into practice by performing the translation and the theater task.